Dissipation of Pulsed Electron Beam in Hydrogen and Oxygen in High Pressure; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Tabaev A.; Kholodnaya G. E. Galina Evgenievna; Sazonov R. V. Roman Vladimirovich; Ponomarev D. V. Denis Vladimirovich (Discharge and Plasma-Beam Technology, 2016)
Title screen